The effect of cosmetics on the skin of the face - Pabijanskaitė, Ugnė; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2023)
Couperosis is a skin condition in which there is a disorder of the skin covering the face with a network of dilated capillaries; it is usually an inherited skin condition. The development of couperosis is influenced by the weakening of capillaries, chronic diseases that predispose to blood circulation disorders. Aim of the study. To assess the effect of cosmetic products on couperose facial skin. Methods. Mixed method research. In 2023, one 58-year-old subject was used for this study, meeting the criteria required for the study: age, with a couperose skin condition, job specifics that would allow not to wear heavy make-up every day, to be in the sun for a long time, not to have allergic reactions to the components of the used products. The following were used for the study: a skin diagnostic device, a customer card, a course of ten procedures with the active substance, repeated weekly. Results. Mixed skin type, deformational aging. Couperosis can be seen on the cheeks, in the wings of the nose, there are telangiectasias in the area of the wings of the nose, on the left cheek of the eye. The skin is dehydrated, sebum secretion is increased in the forehead, nose and chin area. During the procedures, multi-component X active substances are used to reduce the effect of couperose on the skin, moisturize, stimulate skin regeneration, collagen and elastin synthesis, shrink capillaries and strengthen the hydrolipidic barrier. Conclusions. 1. Damaged facial skin is caused by an improper use of cosmetic products and exposure to the external risk factors. 2. The multicomponent, acid-based active substances used to restore the hydrolipidic barrier and improve the condition of couperose skin strengthened capillaries, improved skin metabolism, accelerated cell regeneration, and reduced the harmful effects of couperose on the skin.